Implementation of Complex Proportional Assessment and Rank Order Centroid Methods for Selecting Delivery Services - Trianto, Joko; Dartono, Dartono; Nuraini, Rini; Rusdianto, Hengki (Forum Kerjasama Pendidikan Tinggi, 2023)
Choosing the right delivery service partner is an important thing for companies to consider. This is because the selection of the right delivery service partner can minimize the risks involved. Generally, choosing a delivery partner service is done by looking at the profile of the freight forwarder's partner. It takes time to determine the right delivery service partner. This study aims to apply the Complex Proportional Assessment (COPRAS) and Rank Order Centroid (ROC) methods in a decision support system for selecting delivery service partners to make it easier to make the right decisions and meet needs. The ROC weighting method is used to determine the value of the criteria based on priority. Meanwhile, the COPRAS approach is used to determine the best solution based on an analysis of the existing options through alternative assessments by providing interval-based utility judgments. In the case study conducted, the best alternative was obtained, namely J&T Express with a score of 100, followed by JNE Express with a value of 92.09, SiCepat with a value of 91.89, Ninja Express with a value of 91.42. The COPRAS calculation results on the system developed with the manual calculation results show the same value, this means that the calculations on the system are valid. The usability scores, on the other hand, have an average value of 88.33% and are considered good